Efficient method for isolation of exosomes from raw bovine milk. (4th March 2019) - Yamauchi, Marika; Shimizu, Kaori; Rahman, Matiur; Ishikawa, Hinata; Takase, Hiroshi; Ugawa, Shinya; Okada, Ayaka; Inoshima, Yasuo
Abstract: Objective: This study aimed to establish a rapid and simple method for isolating exosomes from raw bovine milk and to compare the quality of the isolated exosomes with those isolated by a standard method involving ultracentrifugation (UC). Methods: To remove caseins, which are major milk proteins consisting more than 80% of milk protein (35% in human breast milk) and hamper isolation and purification of exosomes, hydrochloride (HCl) was added to milk for isoelectric precipitation (IP). The effects of acidification on morphological features, particle size distribution, surface charge, and exosome surface proteins were analyzed by electron microscopy, tunable resistive pulse sensing (TRPS), and Western blot (WB) analysis, respectively. Results: Electron microscopy showed that some of the exosomes isolated using IP had rough surfaces; most exosomes were successfully isolated without breakage, and their morphological features were similar to those of exosomes isolated by UC. TRPS showed that their surface charge and peaks (mode) for particle size distribution did not significantly differ between both methods. WB analysis using antibodies against the exosome surface marker proteins – milk fat globule-epidermal growth factor 8 (MFG-E8) and CD63 – revealed that the structures of exosome surface proteins were not affected by adding HCl. Conclusions: IP can be used to remove caseins to reduce operation time. This method will be useful for efficient isolation and purification of bovine milk exosomes and contribute to progression of research on health management of dairy cattle and drug delivery systems in human medicine, which require large amounts of milk exosomes.